CLINICAL-NEUROPHYSIOLOGICAL AND MORPHOLOGICAL STUDIES OF CHILDREN WITH CONSEQUENCES OF HYPOXIC - Saidovich, Ergashev Suxrob; Mirxamzayevna, Mamurova Mavludaxon; Temirpulotovich, Turayev Bobir (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: The problem of perinatal brain injury of hypoxic-ischemic genesis remains a critical issue, with a focus on its high mortality rates, significant disability, and impact on neuropsychic and somatic development in children. These injuries lead to difficulties in social adaptation, diagnosis, and treatment. Methods: The study aims to explore current therapeutic measures applied to children with perinatal hypoxic-ischemic damage to the central nervous system (CNS), evaluating their effectiveness in addressing these challenges. Various medical and social factors are examined to understand the limitations in the treatment of such conditions. Results: It is found that the existing therapeutic interventions for children suffering from perinatal hypoxic-ischemic CNS damage are not always sufficiently effective. The analysis highlights the need for better approaches to diagnosis, treatment, and overall care to improve the quality of life and development for affected children. Novelty: This study contributes new insights into the current state of perinatal brain injury treatment and diagnosis, emphasizing the importance of developing more effective therapeutic strategies to combat the long-term effects of hypoxic-ischemic damage in children. The findings suggest areas for further research to address these challenges comprehensively.